PENDAMPINGAN DAN PELATIHAN TEKNIK BENDING TRIPLEK DALAM PENGGUNAAN KLEM “F” - Prabani Setio, Stefanus; Widyastuti, Maria (Universitas katolik Musi Charitas, 2024)
This community service activity aimed to enhance motor skills of people with disabilities. Involving 28 participants from three communities in Semarang and Surabaya, the activity provided training in plywood bending using